APPLICATION OF THE BUSINESS JUDGMENT RULE IN ASSESSING DIRECTOR LIABILITY POST-ACQUISITION BY STATE-OWNED ENTERPRISES - Audrey Adyuta Putri; Nyulistiowati Suryanti (Awang Long Law Review, 2026)
Acquisitions represent a pivotal strategy for publicly listed state-owned enterprises (SOEs) to achieve rapid business expansion and enhance corporate value. However, these transactions carry substantial risks of failure that may expose directors to legal liability claims. This raises a critical question: how should the liability of directors of publicly listed SOEs be assessed when their post-acquisition decisions result in adverse outcomes? This research examines the application of the business judgment rule (BJR) as a legal standard for evaluating directors' liability in the context of post-acquisition decision-making by publicly listed SOEs. Employing a normative juridical approach with statutory and conceptual analysis, this study investigates the challenges of applying the BJR within the distinctive dual mandate of SOEs, pursuing commercial profitability while simultaneously fulfilling public service obligations. The analysis focuses on balancing the need to provide legal protection that enables directors to undertake calculated business risks with the imperative to safeguard state assets and protect public shareholders' interests. The findings reveal that applying the BJR in its conventional form to SOEs presents significant challenges due to potential state intervention, non-commercial objectives, and heightened accountability expectations. This research concludes that a modified application of the BJR is necessary for publicly listed SOEs, supported by strengthened governance frameworks that ensure directors' post-acquisition decisions adhere to principles of prudence, good faith, transparency, and accountability while accommodating the unique characteristics of state ownership.